Design and optimization of an energy storage system for off-grid rural communities - Zain Ul Abddin Soomro; Shoaib Ahmed Khatri; Nayyar Hussain Mirjat; Abdul Hannan Memon; Muhammad Aslam Uqaili; Laveet Kumar (International Journal of Renewable Energy Development, 2026)
Access to reliable electricity remains a significant challenge in various developing countries, specifically in Pakistan, where traditional grid expansion is often economically unfeasible, especially in remote and rural areas, which results in frequent outages and limited access to modern energy services. To address this issue, this research aims to design and optimize an off-grid microgrid system powered by Renewable Energy (RE) sources, specifically solar energy, integrated with an efficient Energy Storage System (ESS) to ensure a continuous supply during low Solar Irradiance ( ), adverse weather conditions, and at night. The proposed off-grid system includes three types of storage technologies: Lithium-Ion Battery (LIB), Sodium-Ion Battery (NIB), and Hydrogen Storage System (HSS). The study employs HOMER Pro to simulate and optimize the system sized as 150 kW. The comprehensive techno-economic analysis is undertaken, and offers two key perspectives, i) System #2 exhibits better technical performance, offering a higher RE fraction and capacity utilization, and ii) System #1 has better economic performance by providing lower Net Present Cost (NPC) and Levelized Cost of Energy (LCOE), Specifically, with the integration of NIBs. These results reveal that the 1.53 $M of NPC, 0.0649 $/kWh of LCOE are the lowest, at RE fraction of 100%, and 0.0977% capacity shortage with 0.0494% of unmet load respectively. A sensitivity analysis is also undertaken to establish the robustness of the proposed off-grid system and the impact of uncertain techno-economic parameters on NPC and LCOE with a variation of ±2%, which enhances the reliability in meeting energy demands. The primary objective of this research is to investigate the potential of NIBs as a future-forward energy storage option, being cost-effective, and derived from abundant, low-cost materials, i.e., Sodium (Na).